Perspective of synaptic protection after post-infarction treatment with statins (2015)
ABSTRACT: Stroke is the second most common cause of death in people over 45 years of age in Colombia and is the leading cause of permanent disability worldwide. Cerebral ischemia is a stroke characterized by decreased blood flow due to the occlusion of one or more cerebral arteries, which can cause memory problems and hemiplegia or paralysis, among other impairments. The literature contains hundreds of therapies (invasive and noninvasive) that exhibit a neuroprotective effect when evaluated in animal models. However, in clinical trials, most of these drugs do not reproduce the previously demonstrated neuroprotective property, and some even have adverse effects that had not previously been detected in animal experimentation. Statins are drugs that inhibit 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, the rate-limiting enzyme in cholesterol synthesis. Several studies have shown that statin therapy in an animal model of focal cerebral ischemia reduces infarct volume, as well as markers of neurodegeneration, activates neuronal survival pathways, and improves performance on learning and memory tests. Given the implied therapeutic benefit and the limited understanding of the mechanism of action of statins in brain repair, it is necessary to address the biochemical and tissue effects of these drugs on synaptic proteins, such as NMDA receptors, synaptic adhesion proteins, and cytoskeletal proteins; these proteins are highly relevant therapeutic targets, which, in addition to giving a structural account of synaptic connectivity and function, are also indicators of cellular communication and the integrity of the blood–brain barrier, which are widely affected in the long term post-cerebral infarct but, interestingly, are protected by statins when administered during the acute phase.